2002
DOI: 10.1083/jcb.200109037
|View full text |Cite
|
Sign up to set email alerts
|

Ras and TGFβ cooperatively regulate epithelial cell plasticity and metastasis

Abstract: Multistep carcinogenesis involves more than six discrete events also important in normal development and cell behavior. Of these, local invasion and metastasis cause most cancer deaths but are the least well understood molecularly. We employed a combined in vitro/in vivo carcinogenesis model, that is, polarized Ha-Ras–transformed mammary epithelial cells (EpRas), to dissect the role of Ras downstream signaling pathways in epithelial cell plasticity, tumorigenesis, and metastasis. Ha-Ras cooperates with transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
626
2
9

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 678 publications
(677 citation statements)
references
References 48 publications
33
626
2
9
Order By: Relevance
“…However, during malignant tumor progression, epithelium-derived tumor cells often escape TGF-b-induced growth control, and once this has occurred, TGF-b promotes tumor progression resulting in increased tumor cell invasion and metastasis . This is often associated with oncogenic Ras-signaling (Janda et al, 2002;Oft et al, 2002). In the present study, TGFb had no effect on proliferation of head and neck SCC cells in culture or on the levels of cyclin-dependent kinase inhibitors p15 (Ink4b) , p21 (Cip1/Waf1) , and p27 (Kip1) .…”
Section: Discussioncontrasting
confidence: 49%
“…However, during malignant tumor progression, epithelium-derived tumor cells often escape TGF-b-induced growth control, and once this has occurred, TGF-b promotes tumor progression resulting in increased tumor cell invasion and metastasis . This is often associated with oncogenic Ras-signaling (Janda et al, 2002;Oft et al, 2002). In the present study, TGFb had no effect on proliferation of head and neck SCC cells in culture or on the levels of cyclin-dependent kinase inhibitors p15 (Ink4b) , p21 (Cip1/Waf1) , and p27 (Kip1) .…”
Section: Discussioncontrasting
confidence: 49%
“…To better understand the effect of MFG-E8 in NMuMG cells, we examined their growth pattern in collagen gels. Embedding of cells in a gel of an extracellular matrix protein allows studying their morphology and underlying biochemical properties in a three-dimensional (3D) environment that mimics the situation encountered by the cells in vivo (Janda et al, 2002). After 6 days in collagen gels, we observed that whereas control cells tended to form elongated structures with minimal side MFG-E8 promotes mammary tumor growth C Carrascosa et al Figure 6C).…”
Section: Mfg-e8 Downregulation In Ras-transformed Mammary Epithelialmentioning
confidence: 80%
“…In several epithelial cell models, cooperation of the Raf/ ERK/MAPK pathway and TGFb signaling is required for induction and maintenance of EMT in vitro and a metastatic phenotype in vivo (Lehmann et al, 2000;Janda et al, 2002a). To investigate the mechanism of how Raf and TGFb signaling cooperate in these processes, we generated EpH4 cells stably expressing an 4HT-inducible RafER construct (EGFP-DRaf1-hbER(YY)) (Woods et al, 1997).…”
Section: Dose-dependent Effects Of Raf Activation On Cell Proliferatimentioning
confidence: 99%
“…In particular, the ability of transforming growth factor b (TGFb) to induce EMT has been correlated with a tumor-promoting role of TGFb during late-stage cancer development, contrasted by TGFb-induced cell cycle arrest and apoptosis induced in normal epithelial cells (Derynck et al, 2002;Grunert et al, 2003). Using fully polarized mammary epithelial cells (EpH4) transformed with oncogenic Ras (Ep2Ras), we showed that a Ras-induced hyperactive extracellular signal-regulated kinase (ERK)/ mitogen-activated protein kinase (MAPK) signaling cooperating with TGFb is required to cause EMT in vitro and in vivo and tumor metastasis in nude mice (Oft et al, 1996;Janda et al, 2002a). In contrast, Ras-induced phosphatidylinositol 3 0 -kinase signaling was required for efficient protection from TGFbinduced apoptosis as well as for rapid tumor growth (Janda et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%